PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN ASING, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN KONSENTRASI TERHADAP KINERJA PERUSAHAAN SUB SEKTOR ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2023 - Febriana Lengi Siprianus; Rochmad Bayu Utomo (Juremi: Jurnal Riset Ekonomi, 2024)
This research was conducted to determine the influence of managerial ownership, foreign ownership, institutional ownership and concentration ownership on the performance of cigarette sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2023 period. The sample selection technique used in this research uses a purposive sampling technique where the sample selected is based on various considerations and certain criteria that are adapted to the research objectives. Based on the specified criteria, the researcher obtained 40 data. The research results show that managerial ownership and foreign ownership have a positive but not significant influence on company performance. Institutional ownership also has no significant effect on performance. However, ownership concentration has a positive and significant effect, indicating that greater ownership concentration can improve company performance. It is hoped that these findings can become a reference for stakeholders in managing ownership structures and strategies for improving company performance in the cigarette sub-sector.